Super absorbent polymer composition and preparation method thereof

By using an additive with a specific structure during the micronization process, the aggregation of superabsorbent polymers is inhibited, improving grinding efficiency and absorption performance, and reducing fine powder generation.

KR103042966B1Active Publication Date: 2026-11-05LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020220140642
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-29
Filing Date
2022-10-27
Publication Date
2026-11-05
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

Superabsorbent polymers face challenges during grinding due to aggregation and clumping, leading to inefficient grinding processability and increased generation of fine powder, which affects the absorption performance and rate of superabsorbent resins.

Method used

Incorporating an additive with a specific structure, represented by Chemical Formula 1, during the micronization process to suppress hydrogel polymer aggregation, improving grinding processability and enhancing absorption performance and rate.

Benefits of technology

The additive effectively prevents particle aggregation, reducing fine powder generation, and enhances the absorption rate and water retention capacity of superabsorbent resins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 112022114043810-PAT00094_ABST
    Figure 112022114043810-PAT00094_ABST
Patent Text Reader

Abstract

The present invention relates to a superabsorbent resin composition and a method for manufacturing the same. More specifically, the invention relates to a method for manufacturing a superabsorbent resin composition that includes an additive of a specific structure to inhibit the aggregation of a hydrogel polymer during a grinding process and to improve grinding processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a superabsorbent resin composition and a method for manufacturing the same. More specifically, the invention relates to a method for manufacturing a superabsorbent resin composition that includes an additive of a specific structure to inhibit the aggregation of a hydrogel polymer during a grinding process and to improve grinding processability. Background Technology

[0003] Super Absorbent Polymer (SAP) is a synthetic polymer material capable of absorbing 500 to 1,000 times its own weight in moisture, and developers name it by different names such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). The above-mentioned super absorbent polymer began to be commercialized for use in physiological devices, and is now widely used as a material for horticultural soil repair agents, waterproofing materials for civil engineering and construction, seedling sheets, freshness preservation agents in the food distribution sector, and compresses.

[0004] These superabsorbent polymers are widely used in the field of hygiene products, such as diapers and sanitary pads. In the above hygiene products, the superabsorbent polymer is generally contained in a dispersed state within the pulp. However, recently, efforts to provide hygiene products such as thinner diapers have been ongoing, and as part of this, the development of so-called pulpless diapers, in which the pulp content is reduced or no pulp is used at all, is being actively pursued.

[0005] As such, in the case of sanitary materials in which the pulp content is reduced or no pulp is used, a relatively high proportion of superabsorbent polymer is included, and superabsorbent polymer particles are inevitably included in multiple layers within the sanitary material. In order for the overall superabsorbent polymer particles included in multiple layers to more efficiently absorb a large amount of liquid, such as urine, the superabsorbent polymer basically needs to exhibit not only high absorption performance but also a fast absorption rate.

[0006] Meanwhile, such superabsorbent resins are generally manufactured through the steps of polymerizing monomers to produce a hydrogel polymer containing a large amount of water, and then coarsely grinding and drying the hydrogel polymer and grinding it into resin particles having a desired particle size. In particular, there has been a problem in that the hydrogel polymers do not easily undergo grinding because the coarsely ground hydrogel polymers tend to aggregate or clump together during the coarse grinding process.

[0007] Accordingly, in addition to improving water retention capacity (CRC), a physical property representing the basic absorption and water retention capacity of superabsorbent resins, and pressure absorption capacity (AUP), which indicates the characteristic of retaining absorbed liquid well even under external pressure, there is a continuous demand for the development of technologies that can increase the absorption rate of superabsorbent resins and technologies that can improve the grinding processability during the process. The problem to be solved

[0009] Accordingly, the present invention relates to a method for preparing a superabsorbent resin composition that includes an additive having a specific structure, which can inhibit aggregation of a hydrogel polymer and improve grinding processability during a grinding process. means of solving the problem

[0011] In order to solve the above problem, the present invention,

[0012] Superabsorbent resin particles comprising a crosslinked polymer of a water-soluble ethylene-based unsaturated monomer having an acidic group and an internal crosslinking agent; and

[0013] A superabsorbent resin composition comprising an additive represented by the following chemical formula 1 is provided:

[0014] [Chemical Formula 1]

[0015]

[0016] In the above chemical formula 1,

[0017] A1, A2, and A3 each independently, single bond, carbonyl, , or and, provided that one or more of these are carbonyl or And, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and It is connected to adjacent R1, R2, and R3, respectively, and

[0018] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and

[0019] n is an integer from 1 to 9.

[0021] In addition, the present invention,

[0022] A step of forming a polymer by cross-linking a water-soluble ethylene-based unsaturated monomer having an acidic group in the presence of an internal cross-linking agent and a polymerization initiator (Step 1);

[0023] A step of neutralizing at least some of the acidic groups of the above polymer (step 2);

[0024] A step of preparing base resin particles by micronizing the polymer in the presence of an additive represented by the following chemical formula 1 (Step 3); and

[0025] A method comprising the step (step 4) of drying the above base resin particles,

[0026] A method for manufacturing a superabsorbent resin composition is provided:

[0027] [Chemical Formula 1]

[0028]

[0029] In the above chemical formula 1,

[0030] A1, A2, and A3 each independently, single bond, carbonyl, , or and, provided that one or more of these are carbonyl or And, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and It is connected to adjacent R1, R2, and R3, respectively, and

[0031] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and

[0032] n is an integer from 1 to 9. Effects of the invention

[0034] According to the superabsorbent resin composition and the method for manufacturing the same of the present invention, the grinding processability can be improved by introducing an additive having a specific structure during the grinding process of the hydrogel polymer to suppress the aggregation of hydrogel polymer particles, and accordingly, the absorption performance and absorption rate of the superabsorbent resin can be improved. Brief explanation of the drawing

[0036] Figure 1 is a flowchart relating to a conventional method for manufacturing a superabsorbent resin. Figure 2 is a photograph showing an example of an evaluation item in the evaluation of particle aggregation characteristics. Specific details for implementing the invention

[0037] The terms used herein are merely for describing exemplary embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this specification, terms such as “comprising,” “comprising,” or “having” are intended to indicate the presence of the implemented features, steps, components, or combinations thereof, and should be understood as not precluding the existence or addition of one or more other features, steps, components, or combinations thereof.

[0038] The present invention is capable of various modifications and may take various forms, and specific embodiments are illustrated and described in detail below. However, this is not intended to limit the invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0039] Hereinafter, a method for manufacturing a superabsorbent resin and a superabsorbent resin will be described in more detail according to specific embodiments of the invention.

[0040] Prior to this, the technical terms used in this specification are intended merely to refer to specific embodiments and are not intended to limit the invention. Furthermore, the singular forms used herein include plural forms unless phrases clearly indicate otherwise.

[0041] The terms "polymer" or "polymer" used in the specification of the present invention refer to a state in which water-soluble ethylene-based unsaturated monomers are polymerized, and may encompass all moisture content ranges or particle size ranges. Among the polymers, a polymer having a moisture content (water content) of about 40 weight% or more in the state before drying after polymerization may be referred to as a hydrogel polymer, and particles obtained by grinding and drying such hydrogel polymers may be referred to as a cross-linked polymer.

[0042] In addition, the term "superabsorbent resin particles" refers to a particulate material comprising a cross-linked polymer in which a water-soluble ethylene-based unsaturated monomer containing an acidic group and at least some of the acidic group is neutralized is polymerized and cross-linked by an internal cross-linking agent.

[0043] Additionally, the term "superabsorbent resin" is used to encompass, depending on the context, a cross-linked polymer formed by polymerizing a water-soluble ethylene-based unsaturated monomer containing acidic groups and having at least some of the acidic groups neutralized, or a base resin in the form of a powder consisting of superabsorbent resin particles formed by grinding the cross-linked polymer, or a state suitable for commercialization obtained by undergoing additional processes, such as surface crosslinking, fine powder reassembly, drying, grinding, classification, etc., with respect to the cross-linked polymer or the base resin. Accordingly, the term "superabsorbent resin composition" can be interpreted as a composition containing a superabsorbent resin, that is, one containing a plurality of superabsorbent resin particles.

[0044] In addition, the term "fine" refers to particles among superabsorbent resin particles having a particle size of less than 150 μm. The particle size of these resin particles can be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.

[0045] In addition, the term "chopping" refers to cutting hydrogel polymers into small, millimeter-sized pieces to increase drying efficiency, and is used to distinguish it from grinding to micrometer or normal particle levels.

[0046] In addition, the term "micronizing" refers to the process of grinding hydrogel polymers to particle sizes of tens to hundreds of micrometers, and is used to distinguish it from "chopping."

[0048] Meanwhile, conventional superabsorbent polymers are manufactured by cross-linking a water-soluble ethylene-based unsaturated monomer having at least some neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator to form a hydrogel polymer, drying the formed hydrogel polymer, and then grinding it to a desired particle size. Typically, a chopping process is performed before the drying process to cut the hydrogel polymer into particles of several millimeters in size to facilitate drying and increase the efficiency of the grinding process. However, due to the adhesiveness of the hydrogel polymer during this chopping process, the hydrogel polymer cannot be ground to the micro-sized particle level and remains in an aggregated gel form. When this aggregated gel-type hydrogel polymer is dried, a plate-shaped dried body is formed, and since a multi-stage grinding process is required to grind it to the micro-sized particle level, there has been a problem in that a large amount of fine powder is generated during this process.

[0049] Specifically, FIG. 1 illustrates a flowchart relating to a conventional method for manufacturing a superabsorbent resin. Referring to FIG. 1, a conventional superabsorbent resin has been manufactured by including the following steps.

[0050] (Neutralization) A step of neutralizing at least some of the acidic groups of a water-soluble ethylene-based unsaturated monomer;

[0051] (Polymerization) A step of forming a hydrogel polymer by cross-linking a water-soluble ethylene-based unsaturated monomer having at least some neutralized acidic groups in the presence of an internal cross-linking agent and a polymerization initiator;

[0052] (Chopping) A step of chopping the above-mentioned hydrogel polymer;

[0053] (Drying) A step of drying the chopped hydrogel polymer; and

[0054] (Grinding / Classification) A step of grinding the above-mentioned dried polymer and classifying it into normal particles and fine powder;

[0055] As described above, the chopped hydrogel polymer has an aggregated gel form with a size of about 1 cm to 10 cm, and this chopped hydrogel polymer is stacked on a belt with a perforated bottom and dried by hot air supplied from the bottom or top. Since the polymer dried by the above drying method exhibits a plate shape rather than a particle shape, the step of classification after grinding has been performed by coarse grinding and classification to ensure that the manufactured particles become normal particles, that is, particles having a particle size of 150 μm to 850 μm, followed by fine grinding and classification. Because the amount of fine powder separated in the final classification step by this manufacturing method is large, amounting to about 10% to about 20% by weight relative to the total weight of the finally manufactured superabsorbent resin, the separated fine powder was reused by mixing it with an appropriate amount of water, reassembling the fine powder, and then feeding it into the chopping step or the drying step.

[0056] However, when the fine powder reassembly mixed with water is reintroduced into the grinding or drying process for the reuse of such fine powder, problems have arisen such as increased equipment load and / or energy consumption, and the remaining fine powder that is not classified has caused a deterioration in the physical properties of the superabsorbent resin.

[0057] Accordingly, the inventors recognized that the amount of fine powder generated in conventional manufacturing methods is significantly affected by the grinding process, and conceived that by adding a surfactant during the chopping process (micronization process) to grind the powder more finely than in the conventional method, and simultaneously controlling aggregation to produce particles in which fine particles are aggregated, the amount of fine powder generated during the manufacturing process can be significantly reduced.

[0059] Meanwhile, when a surfactant is added to a neutralized hydrogel polymer, due to the high water content of the neutralized hydrogel polymer, the surfactant penetrates into the hydrogel polymer rather than remaining at the interface of the hydrogel polymer, resulting in a problem where the surfactant cannot properly perform its role.

[0060] As a result of repeated research to solve this problem, it was confirmed that, unlike conventional methods for manufacturing superabsorbent polymers where polymerization is performed after neutralizing the acidic groups of water-soluble ethylene-based unsaturated monomers, polymerization is performed first in a state where the acidic groups are not neutralized to form a polymer, and then the hydrogel polymer is micronized in the presence of a surfactant and the acidic groups of the polymer are neutralized, or the hydrogel polymer is formed by neutralizing the acidic groups of the polymer and then the hydrogel polymer is micronized in the presence of a surfactant, or the acidic groups present in the polymer are neutralized simultaneously with micronization, so that a large amount of surfactant is present on the surface of the polymer, and the high adhesiveness of the polymer is lowered to prevent the polymer from aggregating excessively and to sufficiently perform the role of controlling the aggregation state to a desired level.

[0061] Accordingly, the amount of fine particles generated during the process can be significantly reduced as the polymer is manufactured into secondary particles in which primary particles are aggregated, and the subsequent grinding and drying processes are carried out under milder conditions.

[0063] In addition, when the polymer is ground in the presence of an additive having a specific structure of Chemical Formula 1 as described above, the hydrophobic functional group portion included in the additive imparts hydrophobicity to the surface of the ground superabsorbent resin particles, thereby alleviating inter-particle friction and increasing the apparent density of the superabsorbent resin, while the hydrophilic functional group portion included in the additive is also bonded to the superabsorbent resin particles, so that the surface tension of the resin is not reduced. Accordingly, the superabsorbent resin produced according to the above-described manufacturing method can have a higher apparent density value while exhibiting an equivalent level of surface tension compared to a resin without such additive.

[0064] In addition, if polymerization is first performed in an unneutralized state to form a polymer, and then the acidic groups present in the polymer are neutralized, it is possible to form a polymer with longer chains, thereby achieving the effect of reducing the content of water-soluble components that exist in an uncrosslinked state due to incomplete crosslinking.

[0065] Since the aforementioned water-soluble components have the property of easily leaching out when the superabsorbent resin comes into contact with liquid, if the content of these components is high, most of the leached components remain on the surface of the superabsorbent resin, making the resin sticky and causing a decrease in liquid permeability. Therefore, it is important to maintain a low content of water-soluble components in terms of liquid permeability.

[0066] In summary, the inventors confirmed that when a polymer is ground by mixing an additive having a specific structure represented by the following chemical formula 1, the aggregation of the ground hydrogel polymer particles is suppressed, thereby improving the processability of the grinding process, and thus completed the present invention. In particular, the particles included in the superabsorbent resin composition prepared according to the above manufacturing method are characterized by exhibiting an improved absorption rate compared to the case where the additive is not used.

[0067] [Chemical Formula 1]

[0068]

[0069] In the above chemical formula 1,

[0070] A1, A2, and A3 each independently, single bond, carbonyl, , or and, provided that one or more of these are carbonyl or And, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and It is connected to adjacent R1, R2, and R3, respectively, and

[0071] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and

[0072] n is an integer from 1 to 9.

[0074] Specifically, the additive represented by the following Chemical Formula 1 simultaneously possesses a hydrophobic functional group and a hydrophilic functional group. Meanwhile, the water-soluble ethylene-based unsaturated monomer has an acidic group (-COOH) and / or a neutralized acidic group (-COO). - Since it contains ), the surface of the polymer produced by polymerization has acidic groups (-COOH) remaining that did not participate in polymerization and / or neutralized acidic groups (-COO). - A large amount of hydrophilic portions are present due to ). Therefore, when the additive is mixed with the polymer, the hydrophilic functional group of the additive is adsorbed onto at least some of the hydrophilic portions present on the surface of the polymer, and the surface of the polymer on which the additive is adsorbed exhibits hydrophobicity due to the hydrophobic functional group located at the other end of the additive. Accordingly, aggregation between the pulverized hydrogel polymer particles can be suppressed.

[0076] Hereinafter, the superabsorbent resin composition of one embodiment will be described in more detail for each component.

[0078] (Superabsorbent resin composition)

[0079] According to one embodiment of the invention, a superabsorbent resin composition is provided, comprising: superabsorbent resin particles comprising a crosslinked polymer of a water-soluble ethylene-based unsaturated monomer having an acidic group and an internal crosslinking agent; and an additive represented by the following chemical formula 1:

[0080] [Chemical Formula 1]

[0081]

[0082] In the above chemical formula 1,

[0083] A1, A2, and A3 each independently, single bond, carbonyl, , or and, provided that one or more of these are carbonyl or And, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and It is connected to adjacent R1, R2, and R3, respectively, and

[0084] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and

[0085] n is an integer from 1 to 9.

[0087] A superabsorbent resin composition of one embodiment comprises superabsorbent resin particles comprising a crosslinked polymer of a water-soluble ethylene-based unsaturated monomer having an acidic group and an internal crosslinking agent. In this case, the crosslinked polymer is formed by crosslinking the water-soluble ethylene-based unsaturated monomer having an acidic group in the presence of an internal crosslinking agent, and has a three-dimensional network structure in which the main chains formed by the polymerization of the monomers are crosslinked by the internal crosslinking agent.

[0088] In other words, the superabsorbent resin composition of one embodiment comprises superabsorbent resin particles comprising a cross-linked polymer between a water-soluble ethylene-based unsaturated monomer having an acidic group and an internal cross-linking agent. Thus, when the cross-linked polymer has a three-dimensional network structure in which the main chains formed by the polymerization of the monomers are cross-linked by the internal cross-linking agent, the water retention capacity and pressure absorption capacity, which are the general physical properties of the superabsorbent resin, can be significantly improved compared to the case in which it has a two-dimensional linear structure that is not further cross-linked by the internal cross-linking agent.

[0090] The above-mentioned water-soluble ethylene-based unsaturated monomer may be any monomer commonly used in the manufacture of superabsorbent resins. As a non-limiting example, the above-mentioned water-soluble ethylene-based unsaturated monomer may be a compound represented by the following chemical formula 2:

[0091] [Chemical Formula 2]

[0092] R-COOM'

[0093] In the above chemical formula 2,

[0094] R is an alkyl group having 2 to 5 carbon atoms containing unsaturated bonds, and

[0095] M' is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0096] Preferably, the monomer may be one or more selected from the group consisting of (meth)acrylic acid and monovalent (alkali) metal salts, divalent metal salts, ammonium salts, and organic amine salts of these acids.

[0097] As such, using (meth)acrylic acid and / or its salt as a water-soluble ethylene-based unsaturated monomer is advantageous because it allows for obtaining a superabsorbent resin with improved absorption. In addition, the above monomers may include maleic anhydride, fumaric acid, crotonic acid, itaconic acid, 2-acryloylethanesulfonic acid, 2-methacryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid or 2-(meth)acrylamide-2-methylpropanesulfonic acid, (meth)acrylamide, N-substituted (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, polyethylene glycol (meth)acrylate, (N,N)-dimethylaminoethyl (meth)acrylate, (N,N)-dimethylaminopropyl (meth)acrylamide, etc.

[0098] Here, the above-mentioned water-soluble ethylene-based unsaturated monomer has acidic groups, and at least some of the acidic groups are neutralized by a neutralizing agent in the neutralization step described later. At this time, basic substances such as sodium hydroxide, potassium hydroxide, and ammonium hydroxide, which can neutralize acidic groups, may be used as the neutralizing agent, and this will be explained in more detail in the manufacturing method section described later.

[0100] In addition, the term 'internal crosslinking agent' used in this specification is used to distinguish it from the surface crosslinking agent for crosslinking the surface of the superabsorbent resin particles described below, and it serves to polymerize by crosslinking the unsaturated bonds of the water-soluble ethylene-based unsaturated monomers described above. Although the crosslinking in the above step proceeds without distinction between the surface and the interior, when the surface crosslinking process of the superabsorbent resin particles described below is carried out, the surface of the finally manufactured superabsorbent resin particles is formed with a structure crosslinked by the surface crosslinking agent, and the interior is formed with a structure crosslinked by the internal crosslinking agent.

[0101] Any compound that enables the introduction of crosslinking bonds during the polymerization of the above-mentioned water-soluble ethylene-based unsaturated monomer can be used as the above-mentioned internal crosslinking agent. As a non-limiting example, the internal crosslinking agent is N,N'-methylenebisacrylamide, trimethylolpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, triarylamine, pentaerythritol trialylether, ethylene glycol Polyfunctional crosslinking agents such as diglycidyl ether, propylene glycol, glycerin, or ethylene carbonate may be used alone or in combination of two or more, but are not limited thereto. Preferably, among these, pentaerythritol trialyl ether may be used.

[0103] The cross-linking polymerization of the above-mentioned water-soluble ethylene-based unsaturated monomer in the presence of such an internal cross-linking agent can be carried out by thermal polymerization, photopolymerization, or copolymerization in the presence of a polymerization initiator, and optionally a thickener, plasticizer, preservative stabilizer, antioxidant, etc., and specific details will be described later.

[0104] These superabsorbent resin particles may have a particle size of about 150 to about 850 μm, and this particle size may be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.

[0106] In addition, the superabsorbent resin composition includes an additive represented by Chemical Formula 1. As described above, the additive is added so that it can be mixed with the polymer and the micronization (chopping) step can be easily performed without aggregation.

[0107] The additive represented by Chemical Formula 1 above is a nonionic surfactant that exhibits excellent surface adsorption performance due to hydrogen bonding with unneutralized polymers, and is therefore suitable for achieving the desired aggregation control effect. On the other hand, in the case of anionic surfactants rather than nonionic surfactants, when mixed with a polymer neutralized by a neutralizing agent such as NaOH or Na2SO4, adsorption occurs via Na+ ions ionized on the carboxyl group substituents of the polymer, and when mixed with an unneutralized polymer, there is a problem in that the adsorption efficiency for the polymer is relatively reduced due to competition with the anions on the carboxyl group substituents of the polymer.

[0108] Specifically, in the additive represented by the above chemical formula 1, the hydrophobic functional group is the terminal functional group R1, R2, or R3 portion (if not hydrogen), and the hydrophilic functional group is the glycerol-derived portion within the chain and the terminal hydroxyl group (A n is a single bond, and at the same time R nIn the case where g is hydrogen, n=1~3) is further included, and the glycerol-derived portion and the terminal hydroxyl group serve as hydrophilic functional groups that improve adsorption performance on the polymer surface. Accordingly, the aggregation of superabsorbent resin particles can be effectively suppressed.

[0110] In the above chemical formula 1, the hydrophobic functional groups R1, R2, and R3 (if not hydrogen) are each independently a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms. At this time, if the R1, R2, and R3 (if not hydrogen) are alkyl or alkenyl having less than 6 carbon atoms, there is a problem that the aggregation control of the crushed particles is not effectively achieved due to the short chain length, and if the R1, R2, and R3 (if not hydrogen) are alkyl or alkenyl having more than 18 carbon atoms, the mobility of the additive may be reduced, so it may not be effectively mixed with the polymer, and there may be a problem that the unit cost of the composition increases due to the increase in the cost of the additive.

[0111] Preferably, R1, R2, and R3 are hydrogen, or if they are straight-chain or branched-chain alkyls having 6 to 18 carbon atoms, they may be 2-methylhexyl, n-heptyl, 2-methylheptyl, n-octyl, n-nonyl, n-decanyl, n-undecanyl, n-dodecanyl, n-tridecanyl, n-tradecanyl, n-tetradecanyl, n-pentadecanyl, n-hexadecanyl, n-heptadecanyl, or n-octadecanyl; or if they are straight-chain or branched-chain alkenyls having 6 to 18 carbon atoms, they may be 2-hexenyl, 2-heptenyl, 2-octenyl, 2-nonenyl, n-dekenyl, 2-undekenyl, 2-dodekenyl, 2-tridecanyl, 2-tetradekenyl, 2-pentadekenyl, 2-hexadekenyl. It may be 2-heptadekenyl or 2-octadekenyl.

[0113] The above additive may be selected from compounds represented by the following chemical formulas 1-1 to 1-14:

[0114] [Chemical Formula 1-1]

[0115]

[0116] [Chemical Formula 1-2]

[0117]

[0118] [Chemical Formula 1-3]

[0119]

[0120] [Chemical Formula 1-4]

[0121]

[0122] [Chemical Formula 1-5]

[0123]

[0124] [Chemical Formula 1-6]

[0125]

[0126] [Chemical Formula 1-7]

[0127]

[0128] [Chemical Formula 1-8]

[0129]

[0130] [Chemical Formula 1-9]

[0131]

[0132] [Chemical Formula 1-10]

[0133]

[0134] [Chemical Formula 1-11]

[0135]

[0136] [Chemical Formula 1-12]

[0137]

[0138] [Chemical Formula 1-13]

[0139]

[0140] [Chemical Formula 1-14]

[0141] .

[0143] The above additive may be included in an amount of 0.01 to 10 parts by weight per 100 parts by weight of a water-soluble ethylene-based unsaturated monomer. If the total content of the additive relative to the monomer in the composition is excessively low, the aggregation control effect by the additive is insufficient, and the composition may contain superabsorbent resin particles that are not ground to the desired particle size. If the total content of the additive is excessively high, the balance of the general physical properties of the superabsorbent resin, such as water retention capacity and pressure absorption capacity, may be reduced.

[0144] The content of the additive in the above superabsorbent resin composition can be measured by first adding 1 g of the superabsorbent resin composition to 1 ml of distilled water, mixing thoroughly for 1 hour until swelling occurs, then filtering to extract only the solution portion, and then performing HPLC analysis to analyze and measure the content of the additive dissolved in the solution portion.

[0145] More specifically, the additive may be 0.01 parts by weight or more, 0.02 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.5 parts by weight or more of the water-soluble ethylene-based unsaturated monomer in an amount of 100 parts by weight or less, 8 parts by weight or less, 5 parts by weight or less, 3 parts by weight or less, or 2 parts by weight or less.

[0147] Meanwhile, at least some of the above additives may be present on the surface of the superabsorbent resin particles. Here, the phrase "at least some of the above additives are present on the surface of the superabsorbent resin particles" means that at least some of the above additives are adsorbed or bound to the surface of the superabsorbent resin particles. Specifically, each of the above additives may be physically or chemically adsorbed to the surface of the superabsorbent resin. More specifically, the hydrophilic functional group of each of the above additives may be physically adsorbed to the hydrophilic portion of the surface of the superabsorbent resin by intermolecular forces such as dipole-dipole interaction. In this way, the hydrophilic portion of each of the above additives is physically adsorbed to the surface of the superabsorbent resin particles and surrounds the surface, while the hydrophobic portion of each additive is not adsorbed to the surface of the resin particles, so that each additive may be coated on the surface of the resin particles in the form of a micelle structure.

[0148] Accordingly, when at least some of the additives are present on the surface of the superabsorbent resin particles, the aggregation phenomenon of clumping between crushed particles during the manufacturing process of the superabsorbent resin composition can be more effectively suppressed compared to when all of the additives of Formula 1 are present inside the superabsorbent resin particles, specifically inside the cross-linked polymer.

[0149] In addition, as at least some of the above additives are present on the surface of the superabsorbent resin particles, the superabsorbent resin composition containing the additives may have an improved absorption rate compared to a composition not containing such additives.

[0151] Meanwhile, if the above superabsorbent resin composition does not further include the surface cross-linking layer described below, it may not include any hydrophilic additives other than a plurality of the above superabsorbent resin particles, the above additive, and the hydrolysate of the above additive generated by the hydrolysis of the above additive during the manufacturing process of the superabsorbent resin.

[0153] Specifically, the superabsorbent resin composition of one embodiment may not include a compound having multiple glucose units containing hydroxyl groups within the molecule, such as microcrystalline cellulose. For example, the superabsorbent resin composition may be AVICEL represented by the following chemical formula 3, which is available from FMC. ® In the case of containing microcrystalline cellulose with an average particle size of 1 to 10 μm, such as PH-101, aggregation between superabsorbent resin particles is not suppressed due to the numerous hydroxyl groups, so the effect of the aforementioned additive may not be effectively expressed.

[0154] [Chemical Formula 3]

[0155]

[0157] In addition, the superabsorbent resin composition of one embodiment may not include hydrophilic additives such as polyethylene glycol, polypropylene glycol, poly(ethylene glycol)-poly(propylene glycol) copolymer, polyoxyethylene lauryl ether carboxylic acid, sodium polyoxyethylene lauryl ether carboxylate, lauryl sulfate, sodium lauryl sulfate, etc. There is a problem in that such additives are not sufficiently adsorbed onto the surface of the cross-linked polymer, so the aggregation between superabsorbent resin particles is not effectively suppressed. Accordingly, when the superabsorbent resin composition contains such hydrophilic additives instead of the additive of Formula 1, the aggregation between particles after grinding the cross-linked polymer is not suppressed, and the superabsorbent resin composition contains a large amount of fine powder while exhibiting low water retention capacity and low apparent density.

[0159] Meanwhile, the superabsorbent resin composition may further include a surface crosslinking layer formed by additionally crosslinking the crosslinking polymer via a surface crosslinking agent on at least a portion of the surface of the superabsorbent resin particles. This is intended to increase the surface crosslinking density of the superabsorbent resin particles, and when the superabsorbent resin particles further include a surface crosslinking layer as described above, they have a structure in which the crosslinking density is higher on the outside than on the inside.

[0160] As the above surface crosslinking agent, any surface crosslinking agent conventionally used in the manufacture of superabsorbent resins may be used without any particular restrictions. For example, the above surface crosslinking agent may be one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol; one or more carbonate compounds selected from the group consisting of ethylene carbonate, propylene carbonate, and glycerol carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; oxazoline compounds; It may include mono-, di-, or polyoxazolidinone compounds; or cyclic urea compounds; etc.

[0161] Specifically, one or more, two or more, or three or more of the surface crosslinking agents described above may be used as the surface crosslinking agents, for example, propylene glycol, ethylene carbonate, and propylene carbonate may be used.

[0163] In addition, the superabsorbent resin composition may have an absorption rate (vortex time) at 24.0°C according to the vortex method at 24.0°C of 30 seconds or less, 27 seconds or less, 25 seconds or less, 20 seconds or less, 15 seconds or less, or 12 seconds or less. Furthermore, since a smaller value for the absorption rate indicates superiority, the lower limit of the absorption rate is theoretically 0 seconds, but it may be, for example, 5 seconds or more, 8 seconds or more, or 10 seconds or more. At this time, the method for measuring the absorption rate of the superabsorbent resin will be explained in more detail in the experimental examples described later.

[0164] In addition, the superabsorbent resin composition may have a centrifugal retention capacity (CRC) measured according to the EDANA method WSP 241.3 of 39 g / g or more, or 40 g / g or more, or 50 g / g or less, or 48 g / g or less, or 45 g / g or less. The method for measuring the above water retention capacity is explained in more detail in the experimental examples described below.

[0165] In addition, the superabsorbent resin composition may have an applied absorption capacity (AUP) at 0.7 psi, measured according to the EDANA method WSP 242.3, of 24.0 g / g or more, 25.0 g / g or more, 26.0 g / g or more, or 24.3 g / g or more, and may be 30 g / g or less, 28.0 g / g or less, or 26.0 g / g or less. The method for measuring the applied absorption capacity will be explained in more detail in the experimental examples described below.

[0167] (Method for manufacturing a superabsorbent resin composition)

[0168] Meanwhile, the above-mentioned superabsorbent resin composition is,

[0169] A step of forming a polymer by cross-linking a water-soluble ethylene-based unsaturated monomer having an acidic group in the presence of an internal cross-linking agent and a polymerization initiator (Step 1);

[0170] A step of neutralizing at least some of the acidic groups of the above polymer (step 2);

[0171] A step of preparing base resin particles by micronizing the polymer in the presence of an additive represented by the following chemical formula 1 (Step 3); and

[0172] The above base resin particles can be manufactured by including a step (step 4) of drying:

[0173] [Chemical Formula 1]

[0174]

[0175] In the above chemical formula 1,

[0176] A1, A2, and A3 each independently, single bond, carbonyl, , or and, provided that one or more of these are carbonyl or And, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and It is connected to adjacent R1, R2, and R3, respectively, and

[0177] R1, R2, and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and

[0178] n is an integer from 1 to 9.

[0180] Hereinafter, the method for manufacturing a superabsorbent resin of one embodiment will be described in more detail step by step.

[0182] (Step 1)

[0183] In a method for manufacturing a superabsorbent resin according to one embodiment, a step is first performed to form a hydrogel polymer by cross-linking a water-soluble ethylene-based unsaturated monomer having an acidic group in the presence of an internal cross-linking agent and a polymerization initiator.

[0184] The above steps may consist of the step of preparing a monomer composition by mixing the water-soluble ethylene-based unsaturated monomer, an internal crosslinking agent, and a polymerization initiator, and the step of forming a polymer by thermal polymerization or photopolymerization of the monomer composition. In this case, the description of the water-soluble ethylene-based unsaturated monomer and the internal crosslinking agent refers to the above description.

[0186] Here, the water-soluble ethylene-based unsaturated monomer has acidic groups. As previously explained, in the manufacture of conventional superabsorbent resins, a monomer in which at least some of the acidic groups were neutralized by a neutralizing agent was cross-linked to form a hydrogel polymer. Specifically, at least some of the acidic groups of the water-soluble ethylene-based unsaturated monomer having acidic groups were neutralized in the step of mixing an internal crosslinking agent, a polymerization initiator, and a neutralizing agent.

[0187] However, according to one embodiment of the present invention, polymerization is first performed to form a polymer while the acidic group of the water-soluble ethylene-based unsaturated monomer is not neutralized.

[0188] Water-soluble ethylene-based unsaturated monomers (e.g., acrylic acid) in which the acid group is not neutralized are in a liquid state at room temperature and have high miscibility with the solvent (water), existing as a mixed solution in the monomer composition. However, water-soluble ethylene-based unsaturated monomers in which the acid group is neutralized are in a solid state at room temperature and have different solubility depending on the temperature of the solvent (water), and the solubility decreases as the temperature decreases.

[0189] As such, water-soluble ethylene-based unsaturated monomers in a state where the acid groups are not neutralized have higher solubility or miscibility with a solvent (water) than monomers in which the acid groups are neutralized, so they do not precipitate even at low temperatures, and thus are advantageous for long-term polymerization at low temperatures. Accordingly, by performing long-term polymerization using the water-soluble ethylene-based unsaturated monomers in a state where the acid groups are not neutralized, it is possible to stably form a polymer with a higher molecular weight and a uniform molecular weight distribution.

[0190] In addition, since it is possible to form polymers with longer chains, it is possible to achieve the effect of reducing the content of water-soluble components that exist in an uncrosslinked state due to incomplete polymerization or crosslinking.

[0191] In addition, if polymerization is performed first to form a polymer while the acidic groups of the monomer are not neutralized, and then the polymer is micronized in the presence of the additive of Formula 1 after neutralization, or micronized in the presence of the additive of Formula 1 and then neutralized, or the acidic groups present in the polymer are neutralized simultaneously with micronization, the additive of Formula 1 is present in large quantities on the surface of the polymer and can sufficiently perform the role of lowering the adhesiveness of the polymer.

[0193] The type of water-soluble ethylene-based unsaturated monomer among the monomer compositions described above is applied in the same manner as described in the superabsorbent resin composition described above. In addition, the concentration of the water-soluble ethylene-based unsaturated monomer can be appropriately adjusted considering the polymerization time and reaction conditions, and can be about 20 to about 60 weight%, or about 20 to about 40 weight%.

[0195] The type of internal crosslinking agent among the monomer compositions described above is applied in the same manner as described in the aforementioned superabsorbent resin composition. In addition, the content of the internal crosslinking agent may be used in an amount of 0.01 to 5 parts by weight per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer. For example, the internal crosslinking agent may be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less, relative to 100 parts by weight of the water-soluble ethylene-based unsaturated monomer. If the content of the upper internal crosslinking agent is excessively low, crosslinking may not occur sufficiently, making it difficult to achieve strength above an appropriate level; conversely, if the content of the upper internal crosslinking agent is excessively high, the internal crosslinking density increases, making it difficult to achieve the desired water retention capacity.

[0196] In addition, the above polymerization initiator may be appropriately selected according to the polymerization method. When using a thermal polymerization method, a thermal polymerization initiator may be used, and when using a photopolymerization method, a photopolymerization initiator may be used. When using a hybrid polymerization method (a method using both heat and light), both a thermal polymerization initiator and a photopolymerization initiator may be used. However, even in the case of a photopolymerization method, a certain amount of heat is generated by light irradiation such as ultraviolet irradiation, and since a certain amount of heat is also generated as the polymerization reaction, which is an exothermic reaction, proceeds, a thermal polymerization initiator may be additionally used.

[0197] The above photopolymerization initiator can be used without limitation on its composition as long as it is a compound capable of forming radicals by light such as ultraviolet light.

[0198] For example, one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone may be used as the photopolymerization initiator. Meanwhile, specific examples of acyl phosphine include diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphineate, etc. A wider variety of photoinitiators is well described in Reinhold Schwalm's book "UV Coatings: Basics, Recent Developments and New Applications" (Elsevier 2007), p. 115, and is not limited to the examples described above.

[0199] In addition, one or more initiators selected from the group consisting of persulfate-based initiators, azo-based initiators, hydrogen peroxide, and ascorbic acid may be used as the thermal polymerization initiator. Specifically, examples of persulfate-based initiators include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8), while examples of azo-based initiators include 2,2-azobis-(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and 2-(carbamoylazo)isobutylonitrile. Examples include 2,2-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride and 4,4-azobis-(4-cyanovaleric acid). A wider variety of thermal polymerization initiators is well described in Odian's book 'Principles of Polymerization' (Wiley, 1981), p. 203, and is not limited to the examples mentioned above.

[0200] This polymerization initiator may be used in an amount of 2 parts by weight or less per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer. That is, if the concentration of the polymerization initiator is excessively low, the polymerization rate may be slowed down and a large amount of residual monomer may be extracted into the final product, which is undesirable. Conversely, if the concentration of the polymerization initiator is higher than the above range, the polymer chains forming the network become shorter, which may lead to a higher content of water-soluble components and a lower pressurized absorption capacity, thereby degrading the physical properties of the resin, which is undesirable.

[0202] The above monomer composition may further include additives such as thickeners, plasticizers, preservative stabilizers, and antioxidants as needed.

[0203] In addition, the monomer composition containing the monomer may be in a solution state dissolved in a solvent such as water, for example, and the solid content in the monomer composition in this solution state, i.e., the concentrations of the monomer, internal crosslinking agent, and polymerization initiator, may be appropriately controlled by taking into account the polymerization time and reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80 weight%, or 15 to 60 weight%, or 30 to 50 weight%.

[0204] When the above monomer composition has a solid content within the range described above, it may be advantageous to control the grinding efficiency during the grinding of the polymer described later, while eliminating the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that appears in the polymerization reaction of a high-concentration aqueous solution.

[0205] The solvent that can be used at this time may be used without limitation in composition as long as it can dissolve the components described above, and, for example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyloractone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide may be used in combination.

[0207] According to one embodiment of the present invention, the step of forming a polymer by performing polymerization on the monomer composition can be performed in a batch-type reactor.

[0208] In a conventional method for manufacturing a superabsorbent resin composition, the polymerization method is broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Typically, thermal polymerization can be carried out in a reactor equipped with a stirring shaft, such as a kneader, while photopolymerization can be carried out in a reactor equipped with a movable conveyor belt or in a flat-bottomed container.

[0209] Meanwhile, the polymerization method described above generally results in the formation of a polymer with a broad molecular weight distribution and a small molecular weight, depending on the short polymerization reaction time (e.g., 1 hour or less).

[0211] Meanwhile, when photopolymerization is carried out in a reactor equipped with a movable conveyor belt or a flat-bottomed vessel, the form of the hydrogel polymer typically obtained is a sheet-like hydrogel polymer with the width of the belt, and the thickness of the polymer sheet varies depending on the concentration and injection speed or amount of the injected monomer composition, but is typically obtained with a thickness of about 0.5 to about 5 cm.

[0212] However, if the monomer composition is supplied to the extent that the thickness of the polymer on the sheet is excessively thin, the production efficiency is low and is undesirable. If the thickness of the polymer on the sheet is increased for productivity, the polymerization reaction does not occur evenly over the entire thickness, making it difficult to form a high-quality polymer.

[0213] In addition, polymerization in a reactor equipped with a conveyor belt and a stirring shaft is carried out continuously as a new monomer composition is supplied to the reactor while the polymerization product moves, so polymers with different polymerization rates are mixed, and consequently, it is difficult to achieve uniform polymerization throughout the monomer composition, which may lead to a decrease in overall physical properties.

[0215] However, according to one embodiment of the present invention, as polymerization is carried out in a stationary manner in a batch reactor, there is less risk of polymers with different polymerization rates being mixed, and accordingly, a polymer having uniform quality can be obtained.

[0216] In addition, the polymerization step is carried out in a batch reactor having a predetermined volume, and the polymerization reaction is carried out for a longer period, for example, 3 hours or more, than when polymerization is carried out continuously in a reactor equipped with a conveyor belt. Despite such a long polymerization reaction time, since polymerization is carried out on water-soluble ethylene-based unsaturated monomers in an unneutralized state, the monomers do not precipitate well even when polymerization is carried out for a long period, and thus it is advantageous to carry out polymerization for a long period.

[0218] Meanwhile, as the polymerization in the batch reactor of the present invention utilizes a thermal polymerization method, the polymerization initiator may be a thermal polymerization initiator among the aforementioned initiators.

[0220] Meanwhile, in one embodiment of the present invention, polymerization can be initiated by adding a reducing agent that forms a redox couple with the initiator.

[0221] Specifically, the initiator and the reducing agent react with each other to form radicals when added to the polymer solution.

[0222] The formed radicals react with the monomers, and since the oxidation-reduction reaction between the initiator and the reducing agent is highly reactive, polymerization is initiated even when only a small amount of the initiator and reducing agent is added, so there is no need to raise the process temperature, making low-temperature polymerization possible and minimizing changes in the physical properties of the polymer solution.

[0223] The polymerization reaction using the above oxidation-reduction reaction can proceed smoothly even at temperatures near or below room temperature (25°C). For example, the polymerization reaction can be carried out at a temperature between 5°C and 25°C, or between 5°C and 20°C.

[0224] In one embodiment of the present invention, when a persulfate-based initiator is used as the initiator, one or more reducing agents selected from the group consisting of sodium metabisulfite (Na2S2O5); tetramethyl ethylenediamine (TMEDA); a mixture of iron(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; and disodium 2-hydroxy-2-sulfinoacteate may be used.

[0225] For example, potassium persulfate may be used as an initiator and disodium 2-hydroxy-2-sulfinoacetate as a reducing agent; ammonium persulfate may be used as an initiator and tetramethylethylenediamine as a reducing agent; or sodium persulfate may be used as an initiator and sodium formaldehyde sulfoxylate as a reducing agent.

[0226] In another embodiment of the present invention, when a hydrogen peroxide-based initiator is used as the initiator, the reducing agent may be one or more selected from the group consisting of ascorbic acid; sucrose; sodium sulfite (Na2SO3) and sodium metabisulfite (Na2S2O5); tetramethyl ethylenediamine (TMEDA); a mixture of iron(II) sulfate and EDTA (FeSO4 / EDTA); sodium formaldehyde sulfoxylate; disodium 2-hydroxy-2-sulfinoacteate; and disodium 2-hydroxy-2-sulfoacteate.

[0227] The polymer obtained by this method can form a polymer with a high molecular weight and a uniform molecular weight distribution as described above by polymerizing using an unneutralized ethylene-based unsaturated monomer, and the content of water-soluble components can be reduced.

[0229] The polymer obtained by such a method is in the form of a hydrogel polymer, and the water content may be 30 to 80 weight%. For example, the water content of the polymer may be 30 weight% or more, or 45 weight% or more, or 50 weight% or more, and 80 weight% or less, or 70 weight% or less, or 60 weight% or less.

[0230] If the moisture content of the polymer is excessively low, it may be difficult to secure an appropriate surface area in the subsequent grinding step, so it may not be effectively ground, and if the moisture content of the polymer is excessively high, the pressure received in the subsequent grinding step increases, making it difficult to grind to the desired particle size.

[0231] Meanwhile, throughout this specification, "moisture content" refers to the amount of water contained relative to the total weight of the polymer, calculated by subtracting the weight of the polymer in a dry state from the weight of the polymer. Specifically, it is defined as a value calculated by measuring the weight loss due to water evaporation in the polymer during the drying process in which the temperature of the polymer in a crumb state is raised by infrared heating. At this time, the drying conditions are set such that the temperature is raised from room temperature to approximately 180°C and then maintained at 180°C, with the total drying time set to 40 minutes, including a 5-minute temperature raising step, to measure the moisture content.

[0233] (Step 2 and Step 3)

[0234] Next, the steps of neutralizing at least some of the acidic groups of the polymer (step 2); and micronizing the polymer in the presence of an additive represented by Formula 1 to produce base resin particles (step 3) are performed.

[0236] First, as the neutralizing agent used in step 2 above, basic substances such as sodium hydroxide, potassium hydroxide, and ammonium hydroxide, which can neutralize acidic groups, may be used.

[0238] In addition, the degree of neutralization, which refers to the extent to which acidic groups included in the polymer are neutralized by the neutralizing agent, may be 50 to 90 mol%, or 60 to 85 mol%, or 65 to 85 mol%, or 65 to 75 mol%. Although the range of the degree of neutralization may vary depending on the final physical properties, if the degree of neutralization is excessively high, the absorption capacity of the superabsorbent resin may decrease, and if the concentration of carboxyl groups on the particle surface is excessively low, surface crosslinking in subsequent processes may be difficult to perform properly, which may result in a decrease in absorption characteristics under pressure or permeability. Conversely, if the degree of neutralization is excessively low, not only is the absorption capacity of the polymer significantly reduced, but it may also exhibit properties similar to elastic rubber, which is difficult to handle.

[0240] Next, the step of micronizing the polymer in the presence of an additive represented by Chemical Formula 1 to produce base resin particles (Step 3) is performed.

[0241] Here, steps 2 and 3 may be performed sequentially, simultaneously, or alternately. That is, a step of micronizing the polymer is performed simultaneously with step 2, or before or after performing step 2, in the presence of a surfactant (step 3).

[0242] The above step is a step of micronizing the polymer in the presence of the additive of Chemical Formula 1, wherein the polymer is not chopped to a millimeter size, but rather a step in which cutting and aggregation into tens to hundreds of micrometers are carried out simultaneously. That is, by imparting appropriate adhesiveness to the polymer, a secondary aggregated particle is produced in the form of an aggregated primary particle cut into tens to hundreds of micrometers. The base resin particle, which is the secondary aggregated particle produced by this step, has a normal particle size distribution and a significantly increased surface area, so the absorption rate can be significantly improved.

[0244] In this way, after mixing the polymer and the additive of Formula 1, the polymer can be micronized in the presence of the additive of Formula 1 to produce base resin particles in the form of secondary aggregated particles that are cut and aggregated while the superabsorbent resin particles and surfactant are mixed.

[0245] The description of the additive represented by Chemical Formula 1 above can be applied in the same way as the description of the superabsorbent resin composition described above.

[0246] Here, "base resin particles" are particles having a moisture content (water content) of about 30 weight% or more, and since the polymer is cut and aggregated into particle form without a drying process, they may have a moisture content of 30 to 80 weight%, preferably 70 to 80 weight%, similar to the polymer.

[0248] Meanwhile, the additive of Formula 1 may be used in an amount of 0.01 to 10 parts by weight per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer used in the crosslinking polymerization for producing the polymer. If the additive of Formula 1 is used in an excessively small amount, it may not be evenly adsorbed onto the surface of the polymer, and re-aggregation of particles may occur after grinding; if the surfactant is used in an excessive amount, the general physical properties of the finally produced superabsorbent resin may be degraded. For example, the additive of Formula 1 may be used in an amount of 0.01 parts by weight or more, 0.015 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, or 1 part by weight or less, per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer.

[0250] The method of mixing the additive of Formula 1 into the polymer is not particularly limited as long as it is a method that can evenly mix them into the polymer, and can be appropriately adopted and used. Specifically, the additive of Formula 1 may be mixed dry, dissolved in a solvent and mixed in a solution state, or the additive of Formula 1 may be melted and then mixed.

[0251] For example, the additive of Formula 1 above may be mixed in the form of a solution dissolved in a solvent. At this time, any type of solvent, whether inorganic or organic, can be used without limitation, but water is the most suitable considering the ease of the drying process and the cost of the solvent recovery system. In addition, the solution may be prepared by mixing the additive of Formula 1 and the polymer in a reaction vessel, by placing the polymer into a mixer and spraying the solution, or by continuously supplying the polymer and the solution to a continuously operated mixer for mixing.

[0253] Meanwhile, according to one embodiment of the present invention, steps 2 and 3 may be performed sequentially, simultaneously, or alternately.

[0254] That is, a neutralizing agent may be added to the polymer to neutralize the acidic groups first, and then an additive of Formula 1 may be added to the neutralized polymer to micronize the polymer mixed with the additive, or the neutralizing agent and the additive may be added to the polymer simultaneously to perform neutralization and micronization of the polymer. Alternatively, the additive may be added first and the neutralizing agent subsequently. Alternatively, the neutralizing agent and the additive may be added alternately. Alternatively, the additive may be added first to micronize, then the neutralizing agent may be added to neutralize, and then an additional additive may be added to the neutralized hydrogel polymer to perform an additional micronization process.

[0255] Meanwhile, to ensure even neutralization of the entire polymer, it may be desirable to leave a certain time difference between the addition of the neutralizing agent and the micronization process.

[0257] At least some to a substantial amount of the additive of Chemical Formula 1 above may be present on the surface of the base resin particles.

[0258] Here, the meaning that the additive of Formula 1 is present on the surface of the base resin particle means that at least some or a substantial amount of the additive of Formula 1 is adsorbed or bound to the surface of the base resin particle. Specifically, the additive of Formula 1 may be physically or chemically adsorbed on the surface of the base resin particle. More specifically, the hydrophilic functional group of the additive of Formula 1 may be physically adsorbed to the hydrophilic portion of the surface of the base resin particle by intermolecular forces such as dipole-dipole interaction. In this way, the hydrophilic portion of the additive of Formula 1 is physically adsorbed to the surface of the base resin particle and surrounds the surface, while the hydrophobic portion of the additive of Formula 1 is not adsorbed to the surface of the base resin particle, so that the base resin particle may be coated with the additive of Formula 1 in the form of a micelle structure. This is because the additive of Formula 1 is not introduced during the polymerization process of the water-soluble ethylene-based unsaturated monomer, but is introduced during the micronization stage after polymer formation. Compared to the case where the additive of Formula 1 is introduced during the polymerization process and exists inside the polymer, it can faithfully perform the role of a surfactant, and pulverization and aggregation occur simultaneously, allowing for the acquisition of particles with a large surface area in the form of aggregated fine particles.

[0260] According to one embodiment, the step of manufacturing the base resin particles (step 3) can be performed using a micronization device.

[0261] The above-described atomizing device comprises: a body portion including a transfer space in which a mixture of a polymer and an additive is transferred; a screw member rotatably installed inside the transfer space to move the mixture; a drive motor providing rotational driving force to the screw member; and a cutter member installed in the body portion and including a porous plate having a plurality of holes formed therein, which grinds the mixture while discharging it to the outside of the body portion.

[0263] According to one embodiment, steps 2 and 3 are performed sequentially, simultaneously, or alternately, and this can be performed using a micronization device.

[0264] In this case, the atomizing device further includes a neutralizing agent spray nozzle installed inside the body part, so that the neutralizing agent is sprayed through the neutralizing agent spray nozzle, thereby enabling steps 2 and 3 to be performed sequentially, simultaneously, or alternately.

[0265] Specifically, a neutralizing agent is introduced into the body through the neutralizing agent injection nozzle to neutralize at least some of the acidic groups of the polymer having acidic groups in the mixture. Specifically, in the atomization device, a neutralizing agent is introduced into the body through the neutralizing agent injection nozzle to neutralize at least some of the acidic groups of the polymer having acidic groups in the mixture, while simultaneously the mixture is pulverized (atomized) as it is discharged to the outside of the body through a porous plate.

[0266] Preferably, the neutralizing agent ground at the neutralizing agent injection nozzle can be injected adjacent to the porous plate; in this case, it is desirable that the neutralizing agent acts as a slip agent within the mixture when the mixture is discharged through the holes of the porous plate while simultaneously performing the neutralization process, thereby reducing the load on the holes.

[0268] Preferably, the cutter member of the atomizing device comprises a porous plate and a cutting knife positioned adjacent to the porous plate at the outlet side of the body part, and the mixture is more effectively crushed and atomized by the cutting knife after passing through the porous plate.

[0269] In the above-described atomizing device, the cutter member may include a plurality of porous plates and a plurality of cutting knives. The arrangement order of the plurality of porous plates and the plurality of cutting knives is not particularly limited, and they may be arranged sequentially, arranged intersectingly, arranged continuously, arranged continuously, or arranged continuously.

[0270] As described above, by including a plurality of porous plates and cutting knives, multiple atomization steps can be performed within a single atomization device. Meanwhile, a plurality of neutralizing agent spray nozzles may be arranged adjacent to one or more of the plurality of porous plates and cutting knives, and it is preferable to arrange the neutralizing agent spray nozzles adjacent to the porous plates to improve slip properties.

[0271] In the above-described atomizing device, the hole size formed in the porous plate may be 0.1 mm to 30 mm. Preferably, it may be 0.5 mm to 25 mm, 1 mm to 20 mm, or 1 mm to 10 mm. By using a porous plate having the above hole size, base resin particles having a desired particle size can be manufactured. When the cutter member includes a plurality of porous plates as described above, the hole size formed in each porous plate may satisfy the aforementioned range, and may be the same or different from one another.

[0273] According to one embodiment of the invention, step 3 may be performed multiple times, which may be performed using multiple atomizing devices, or using a single atomizing device comprising multiple porous plates and / or multiple cutting knives, or some of the multiple atomizing devices may comprise multiple porous plates and / or multiple cutting knives. The atomizing step may preferably be performed 1 to 6 times or 1 to 4 times. When step 3 is performed multiple times, the additive may be additionally introduced multiple times.

[0275] The step of micronizing the polymer to produce base resin particles (Step 3) can be performed such that the average particle size of the base resin particles is 50 μm to 600 μm, and preferably, it can be micronized to 100 μm to 500 μm, 150 μm to 450 μm, or 200 μm to 400 μm. By satisfying the above particle size range, the polymer is produced as secondary particles in the form of aggregated primary particles, and as the grinding and drying processes are subsequently carried out under milder conditions, the amount of fine powder generated during the process can be significantly reduced.

[0276] In the present invention, the average particle size “Dn” refers to the particle size or particle diameter at the n% point of the cumulative distribution of the number of particles according to particle size. That is, D50 represents the particle size at the 50% point of the cumulative distribution of the number of particles according to particle size, D90 represents the particle size at the 90% point of the cumulative distribution of the number of particles according to particle size, and D10 represents the particle size at the 10% point of the cumulative distribution of the number of particles according to particle size. The above Dn can be measured using a laser diffraction method, etc. Specifically, after dispersing the powder to be measured in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) and the difference in diffraction patterns according to particle size is measured as the particles pass through the laser beam to calculate the particle size distribution. D10, D50, and D90 can be measured by calculating the particle size at the point where the cumulative distribution of the number of particles according to particle size in the measuring device reaches 10%, 50%, and 90%.

[0278] (Step 4)

[0279] Next, the method includes a step (step 4) of drying the base resin particles. Through this, a superabsorbent resin composition containing superabsorbent resin particles and an additive represented by Chemical Formula 1 can be prepared.

[0280] The above drying can be performed so that the moisture content of each of the plurality of superabsorbent resin particles included in the manufactured superabsorbent resin composition is about 10 weight% or less, specifically about 0.1 to about 10 weight%.

[0281] At this time, the drying of the crushed material can be performed using a moving type. This moving type drying is distinguished from fixed-bed type drying by the presence or absence of material flow during drying.

[0283] In a conventional method for manufacturing superabsorbent resins, the drying step is generally performed until the moisture content of the superabsorbent resin particles becomes less than 10 wt%. However, the present invention controls aggregation by performing a micronization step in the presence of a chemical formula 1 acid additive, thereby drying the superabsorbent resin particles so that their moisture content becomes 10 wt% to 20 wt%, preferably 10 wt% to 25 wt%. However, the present invention is not limited thereto. Accordingly, there is an advantage in that the generation of fine particles can be fundamentally prevented by exhibiting a high moisture content. Furthermore, it is desirable to be able to improve the absorption rate of the final superabsorbent resin composition.

[0284] To this end, the drying step is performed using a moving type drying method at a relatively low temperature. This moving type drying is distinguished from fixed-bed type drying by the presence or absence of material flow during drying; it is desirable as it prevents aggregation among the finely chopped water-absorbent resin particles within the pulverized material to be dried and enables the drying to be completed within a short period of time.

[0286] To this end, the drying step is performed by drying in a moving type at a relatively low temperature. This moving type drying is distinguished from fixed-bed type drying by the presence or absence of material flow during drying; it is desirable as it prevents aggregation among the shredded base resin particles within the pulverized material to be dried and enables the drying to be completed within a short period of time.

[0287] Specifically, the aforementioned moving-type drying refers to a method of drying a material while mechanically stirring it. In this case, the direction in which the hot air passes through the material may be the same as or different from the direction of circulation of the material. Alternatively, the material may circulate inside the dryer, and the material may be dried by passing a heat transfer fluid through a separate pipe outside the dryer. Meanwhile, fixed-bed type drying refers to a method of drying in which the material to be dried is stationary on a surface, such as a perforated steel plate, and hot air passes through the material from bottom to top.

[0289] The step of drying the base resin particles (step 4) can be performed using a commonly used fluidized dryer without special limitations, for example, a horizontal-type mixer, a rotary kiln, a paddle dryer, or a steam tube dryer.

[0291] The drying step (step 4) above can be performed at a relatively low temperature of 150°C or lower, preferably at 100°C to 150°C, 100°C to 130°C, or 105°C to 115°C, and even if performed at a low temperature as above, superabsorbent resin particles having the desired particle size and physical properties without the desired aggregation can be produced.

[0292] Meanwhile, the above drying temperature may be the internal operating temperature at which the material to be dried is introduced into the fluidized drying device used, and this may be controlled by passing a heat transfer fluid (heat transfer oil) through a separate pipe outside the dryer, but is not limited thereto.

[0294] The above drying step (step 4) can be performed for 30 to 80 minutes, or for 30 to 60 minutes or 40 to 50 minutes, and even if the drying step is performed for a short time at a relatively low temperature, superabsorbent resin particles having the desired particle size and physical properties can be produced because there is less aggregation between the chopped polymer resin particles in the crushed material to be dried.

[0296] (Additional step)

[0297] Subsequently, the method for manufacturing a superabsorbent resin composition according to one embodiment of the invention may further include the step of grinding and classifying the superabsorbent resin particles as needed.

[0298] Specifically, the grinding step can be performed by grinding the dried superabsorbent resin particles to have a particle size at the level of normal particles, i.e., a particle diameter of 150 μm to 850 μm.

[0299] The grinder used for this purpose may specifically be a vertical pulverizer, turbo cutter, turbo grinder, rotary cutter mill, cutter mill, disc mill, shred crusher, crusher, chopper, or disc cutter, but is not limited to the examples described above.

[0300] Alternatively, a grinder such as a pin mill, hammer mill, screw mill, roll mill, disc mill, or jog mill may be used, but is not limited to the examples described above.

[0302] Meanwhile, in the manufacturing method of the present invention, superabsorbent resin particles with a smaller particle size distribution than in the conventional chopping step can be realized in the micronization step, and since the moisture content after drying is maintained relatively high at 10 weight% or more when moving-type drying is performed, a superabsorbent resin with a very high content of normal particle sizes of 150 μm to 850 μm can be formed even when grinding is performed under mild conditions with less grinding force, and the fine particle generation ratio can be significantly reduced.

[0303] The superabsorbent resin particles manufactured as described above may contain 80% or more by weight, 85% or more by weight, 89% or more by weight, 90% or more by weight, 92% or more by weight, 93% or more by weight, 94% or more by weight, or 95% or more by weight of superabsorbent resin particles having a particle size of 150 μm to 850 μm relative to the total weight. The particle size of these resin particles can be measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 220.3 method.

[0304] In addition, the superabsorbent resin particles may contain fine particles having a particle size of less than 150 μm relative to the total weight in an amount of less than about 20 wt%, less than about 18 wt%, less than about 15 wt%, less than about 13 wt%, less than about 10 wt%, specifically less than about 5 wt%, and more specifically less than about 3%. This is in contrast to having more than about 20 wt% to about 30 wt% of fine particles when manufacturing a superabsorbent resin according to a conventional manufacturing method.

[0306] Next, a method for manufacturing a superabsorbent resin according to one embodiment of the invention may include the step of manufacturing superabsorbent resin particles by thermally crosslinking the surface of the base resin powder in the presence of surface crosslinking.

[0307] The above surface crosslinking step induces a crosslinking reaction on the surface of the base resin powder in the presence of a surface crosslinking agent, so that the unsaturated bonds of the water-soluble ethylene-based unsaturated monomers remaining on the surface without being crosslinked are crosslinked by the surface crosslinking agent, thereby forming a superabsorbent resin with a high surface crosslinking density.

[0308] Specifically, a surface crosslinking layer can be formed through a heat treatment process in the presence of a surface crosslinking agent. During the heat treatment process, the surface crosslinking density, i.e., the external crosslinking density, increases, while the internal crosslinking density remains unchanged. Consequently, the superabsorbent resin with the manufactured surface crosslinking layer has a structure in which the external crosslinking density is higher than the internal one.

[0309] The above surface crosslinking process can be performed at a temperature of about 80°C to about 250°C. More specifically, the above surface crosslinking process can be performed at a temperature of about 100°C to about 220°C, or about 120°C to about 200°C, for about 20 minutes to about 2 hours, or about 40 minutes to about 80 minutes. When the above-described surface crosslinking process conditions are satisfied, the surface of the superabsorbent resin particles is sufficiently crosslinked, and the pressure absorption capacity can be increased.

[0310] By satisfying these surface crosslinking process conditions (in particular, temperature increase conditions and reaction conditions at the maximum reaction temperature), a superabsorbent resin that appropriately meets physical properties such as superior absorption rate can be manufactured.

[0311] The means for raising the temperature for the surface crosslinking reaction are not particularly limited. Heating can be achieved by supplying a heat medium or by directly supplying a heat source. In this case, types of heat mediums that can be used include heated fluids such as steam, hot air, and hot oil, but are not limited thereto. Furthermore, the temperature of the supplied heat medium can be appropriately selected considering the medium type, the heating rate, and the target temperature. Meanwhile, directly supplied heat sources include heating via electricity and heating via gas, but are not limited to the examples described above.

[0313] Meanwhile, as the surface crosslinking agent included in the above surface crosslinking agent composition, any surface crosslinking agent conventionally used in the manufacture of superabsorbent resins may be used without any particular restrictions. For example, the above surface crosslinking agent may be one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol, and glycerol; one or more carbonate-based compounds selected from the group consisting of ethylene carbonate and propylene carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; oxazoline compounds; It may include mono-, di-, or polyoxazolidinone compounds; or cyclic urea compounds; etc. Preferably, the same as the internal crosslinking agent described above may be used, and for example, alkylene glycol diglycidyl ether compounds such as ethylene glycol diglycidyl ether may be used.

[0314] In the above surface crosslinking step, a surface crosslinking agent composition comprising an alcohol-based solvent and water in addition to the surface crosslinking agent may be used.

[0315] Such a surface crosslinking agent may be used in an amount of 0.001 to 2 parts by weight per 100 parts by weight of superabsorbent resin particles. Preferably, the amount may be 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.02 parts by weight or more, and may be used in an amount of 0.5 parts by weight or less, or 0.3 parts by weight or less. By adjusting the content range of the surface crosslinking agent to the range described above, a superabsorbent resin exhibiting excellent absorption performance and various physical properties such as liquid permeability can be manufactured.

[0317] Meanwhile, the above-mentioned surface crosslinking agent is added to superabsorbent resin particles in the form of a surface crosslinking agent composition containing it, and there are no specific limitations on the composition of the method of adding such a surface crosslinking agent composition. For example, methods such as placing the surface crosslinking agent composition and the superabsorbent resin particles into a reaction vessel and mixing them, spraying the surface crosslinking agent composition onto the superabsorbent resin particles, or continuously supplying and mixing the superabsorbent resin particles and the surface crosslinking agent composition into a continuously operated mixer may be used.

[0318] In addition, the surface crosslinking agent composition may further include water and / or a hydrophilic organic solvent as a medium. This provides the advantage that the surface crosslinking agent, etc., can be evenly dispersed on the base resin powder. At this time, the content of water and the hydrophilic organic solvent can be applied by adjusting the addition ratio to 100 parts by weight of superabsorbent resin particles for the purpose of inducing even dissolution / dispersion of the surface crosslinking agent, preventing clumping of the base resin powder, and optimizing the surface penetration depth of the surface crosslinking agent.

[0320] Meanwhile, in order to further improve liquid permeability and other properties, the method for manufacturing a superabsorbent resin according to one embodiment of the invention may further use aluminum salts, such as aluminum sulfate salts, and other various polyvalent metal salts during surface crosslinking. Such polyvalent metal salts may be included on the surface crosslinking layer of the finally manufactured superabsorbent resin.

[0322] According to one embodiment of the present invention, after the step of forming a surface cross-linked layer on at least a portion of the surface of the superabsorbent resin particles, the process may further include one or more steps of: a cooling step of cooling the superabsorbent resin particles having the surface cross-linked layer formed thereon; a watering step of adding water to the superabsorbent resin particles having the surface cross-linked layer formed thereon; and a post-treatment step of adding an additive to the superabsorbent resin particles having the surface cross-linked layer formed thereon. In this case, the cooling step, the watering step, and the post-treatment step may be performed sequentially or simultaneously.

[0323] The additives introduced in the above post-treatment step may include permeability enhancers, anti-caking agents, fluidity enhancers, and antioxidants, but the present invention is not limited thereto.

[0324] By selectively performing the above cooling step, water hydration step, and post-treatment step, the water content of the final superabsorbent resin can be improved, and a higher quality superabsorbent resin product can be manufactured.

[0326] According to another embodiment of the present invention, a composition of a superabsorbent resin manufactured by the above manufacturing method is provided.

[0327] The superabsorbent resin composition manufactured by the above manufacturing method achieves a high water content without a separate additional water addition process or additive input process, thereby providing a superabsorbent resin with a low fine particle content and excellent absorption properties such as water retention capacity (CRC) and pressure absorption capacity (AUP) that are equivalent to or higher than those of superabsorbent resins manufactured by conventional methods, while simultaneously having a low water-soluble component (EC) content, which provides excellent absorption rate and other properties.

[0329] The operation and effects of the invention will be described in more detail below through specific embodiments. However, these embodiments are merely examples of the invention and do not define the scope of the invention.

[0331] Example - Preparation of a superabsorbent resin composition

[0332] Example 1

[0333] (Step 1) 1,000 g of acrylic acid, 3.5 g of pentaerythritol trialyl ether as an internal crosslinking agent, and 2,260 g of water were mixed in a 5 L glass container equipped with a stirrer and a thermometer, and stirred while maintaining the temperature at 5°C. Nitrogen was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to replace the atmosphere with nitrogen. Next, 13 g of a 0.3% aqueous hydrogen peroxide solution, 15 g of a 1% aqueous ascorbic acid solution, and 30 g of a 2% aqueous 2,2'-azobis-(2-amidinopropane) dihydrochloric acid solution were added as polymerization initiators, and simultaneously, 15 g of a 0.01% aqueous iron sulfate solution was added as a reducing agent to initiate polymerization. After the temperature of the mixture reached 85°C, the polymer was obtained by polymerizing at 90±2°C for about 3 hours. The water content of the polymer was about 70 wt%.

[0334] (Steps 2 and 3) 1.19 g of compound A-1 of Table 1 was water-dispersed in 52.27 g of water as an additive of Chemical Formula 1 (preparation of a 2 wt% water dispersion), and this was mixed with 1,000 g of the polymer obtained in Step 1.

[0335] The above mixture was passed once through a first atomization device equipped with a porous plate having a plurality of holes with a hole size of 6 mm to perform a first atomization process.

[0336] Next, the second, third, and fourth micronization processes were performed by repeatedly feeding the porous plate, which includes a plurality of holes with a hole size of 4 mm, into a second micronization device a total of three times.

[0337] In the above second atomization process, 400g of a 32% NaOH aqueous solution was introduced through a neutralizing agent nozzle placed adjacent to the porous plate, and the neutralization process was performed along with the atomization.

[0338] In the above third atomization process, 37.5g of a 15% aqueous Na2SO4 solution was introduced through a neutralizing agent nozzle placed adjacent to the porous plate, and the neutralization process was performed along with atomization.

[0339] Finally, in the fourth micronization process, the micronization process was performed without adding a neutralizing agent or surfactant to obtain base resin particles.

[0340] The degree of neutralization of the above base resin particles was 70 mol%.

[0341] (Step 4) Afterward, 1,000 g of the base resin particles were fed into a rotary mixer fluid dryer rotating at 100 rpm. Drying was performed for 60 minutes while maintaining the internal temperature of the dryer at 105°C to obtain superabsorbent resin particles. The moisture content of the superabsorbent resin particles was 11 wt%.

[0343] Example 2

[0344] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-2 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0345] After drying in step 4, the moisture content of the final superabsorbent resin particles was 11 wt%.

[0347] Example 3

[0348] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-3 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0349] After drying in step 4, the moisture content of the final superabsorbent resin particles was 11 wt%.

[0351] Example 4

[0352] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-4 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0353] After drying in step 4, the moisture content of the final superabsorbent resin particles was 11 wt%.

[0355] Example 5

[0356] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-5 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0357] After drying in step 4, the moisture content of the final superabsorbent resin particles was 14 wt%.

[0359] Example 6

[0360] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-6 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0361] After drying in step 4, the moisture content of the final superabsorbent resin particles was 14 wt%.

[0363] Example 7

[0364] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-7 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0365] After drying in step 4, the moisture content of the final superabsorbent resin particles was 11 wt%.

[0367] Example 8

[0368] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-8 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0369] After drying in step 4, the moisture content of the final superabsorbent resin particles was 12 wt%.

[0371] Example 9

[0372] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-9 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0373] After drying in step 4, the moisture content of the final superabsorbent resin particles was 13 wt%.

[0375] Example 10

[0376] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-10 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0377] After drying in step 4, the moisture content of the final superabsorbent resin particles was 11 wt%.

[0379] Example 11

[0380] (Step 1) 1,000 g of acrylic acid, 3.5 g of pentaerythritol trialyl ether as an internal crosslinking agent, and 2,260 g of water were mixed in a 5 L glass container equipped with a stirrer and a thermometer, and stirred while maintaining the temperature at 5°C. Nitrogen was introduced into the glass container containing the mixture at 1,000 cc / min for 1 hour to replace the atmosphere with nitrogen. Next, 13 g of a 0.3% aqueous hydrogen peroxide solution, 15 g of a 1% aqueous ascorbic acid solution, and 30 g of a 2% aqueous 2,2'-azobis-(2-amidinopropane) dihydrochloric acid solution were added as polymerization initiators, and simultaneously, 15 g of a 0.01% aqueous iron sulfate solution was added as a reducing agent to initiate polymerization. After the temperature of the mixture reached 85°C, the polymer was obtained by polymerizing at 90±2°C for about 3 hours. The water content of the polymer was about 70 wt%.

[0381] (Steps 2 and 3) 0.595 g of compound A-1 of Table 1 was water-dispersed in 52.27 g of water as an additive of Chemical Formula 1 (preparation of a 2 wt% water dispersion), and this was mixed with 1,000 g of the polymer obtained in Step 1.

[0382] The above mixture was passed once through a first atomization device equipped with a porous plate having a plurality of holes with a hole size of 6 mm to perform a first atomization process.

[0383] Next, the second, third, and fourth micronization processes were performed by repeatedly feeding the porous plate, which includes a plurality of holes with a hole size of 4 mm, into a second micronization device a total of three times.

[0384] In the above second atomization process, 400g of a 32% NaOH aqueous solution was introduced through a neutralizing agent nozzle placed adjacent to the porous plate, and the neutralization process was performed along with the atomization.

[0385] In the above third atomization process, 37.5g of a 15% aqueous Na2SO4 solution was introduced through a neutralizing agent nozzle placed adjacent to the porous plate, and the neutralization process was performed along with atomization.

[0386] Finally, in the fourth micronization process, 0.595 g of compound A-11 of Table 1 was water-dispersed in 52.27 g of water as an additive of Chemical Formula 1 (preparing a 2 wt% aqueous dispersion), and this was fed into a second micronization apparatus containing the mixture obtained from the third micronization process to perform the fourth micronization process and produce base resin particles. The degree of neutralization of the base resin particles was 70 mol%.

[0387] (Step 4) Afterwards, 1,000 g of the base resin particles were fed into a rotary mixer fluid dryer rotating at 100 rpm. Drying was performed for 60 minutes while maintaining the internal temperature of the dryer at 105℃ to obtain high absorbent resin particles.

[0388] After drying in step 4 above, the moisture content of the final superabsorbent resin particles was 12 wt%.

[0390] Example 12

[0391] A superabsorbent resin composition was prepared using the same method as in Example 11, except that in the first micronization step of Example 11, compound A-1 of Formula 1 was used as the additive, and in the fourth micronization step, compound A-2 of Table 1 was used instead of compound A-11 of Formula 1 as the additive.

[0392] After drying in step 4, the moisture content of the final superabsorbent resin particles was 10 wt%.

[0394] Example 13

[0395] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-12 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0396] After drying in step 4, the moisture content of the final superabsorbent resin particles was 14 wt%.

[0398] Example 14

[0399] A superabsorbent resin composition was prepared using the same method as in Example 1, except that compound A-13 of Table 1 was used instead of compound A-1 as the additive of Formula 1 in Example 1.

[0400] After drying in step 4, the moisture content of the final superabsorbent resin particles was 14 wt%.

[0402] Example 15

[0403] A superabsorbent resin composition was prepared using the same method as in Example 1, except that 0.595 g of the A-12 compound used in Example 13 and 0.595 g of the A-13 compound used in Example 14 were mixed as additives of Chemical Formula 1 to use a total of 1.19 g of additives.

[0404] After drying in step 4, the moisture content of the final superabsorbent resin particles was 13 wt%.

[0406] Example 16

[0407] A superabsorbent resin composition was prepared using the same method as in Example 13, except that the content of A-12 as an additive of Formula 1 in Example 13 was increased to 2.38 g.

[0408] After drying in step 4, the moisture content of the final superabsorbent resin particles was 12 wt%.

[0410] Comparative Example 1

[0411] A superabsorbent resin composition was prepared in the same way as in Example 1, except that the additive of Formula 1 was not used.

[0413] Comparative Examples 2 to 6, 8 and 9

[0414] A superabsorbent resin composition was prepared in the same manner as in Example 1, except that the additive of Formula 1 was used as the additive listed in Table 1 below.

[0416] Comparative Example 7

[0417] A monomer composition was prepared by mixing 100 g (1.388 mol) of acrylic acid, 0.16 g of internal crosslinking agent polyethylene glycol diacrylate (Mn= 508), 0.008 g of photopolymerization initiator diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, 0.12 g of thermal polymerization initiator sodium persulfate, and 123.5 g of 32% caustic soda solution at room temperature in a 3L glass container equipped with a stirrer and a thermometer (degree of neutralization of acrylic acid: 70 mol%, solid content: 45 wt%).

[0418] Subsequently, the monomer composition was supplied at a speed of 500 to 2000 mL / min onto a conveyor belt with a width of 10 cm and a length of 2 m, rotating at a speed of 50 cm / min. Then, simultaneously with the supply of the monomer composition, ultraviolet light with an intensity of 10 mW / cm2 was irradiated to carry out the polymerization reaction for 60 seconds, thereby obtaining a hydrogel polymer with a water content of approximately 55 wt%.

[0419] Next, the hydrogel polymer obtained through the above polymerization reaction was ground using a meat chopper without additives. At this time, the water content of the hydroabsorbent resin particles contained in the final ground material was 55 wt%.

[0420] Subsequently, the above-mentioned crushed material was dried by using a convection oven capable of vertical airflow transfer to flow hot air at 185°C from bottom to top for 20 minutes and then from top to bottom for 20 minutes, thereby producing a superabsorbent resin having a final superabsorbent resin particle moisture content of 25 wt% after drying.

[0422] division Step 3 additives Example 1 (A-1) Example 2 (A-2) Example 3 (A-3) Example 4 (A-4) Example 5 (A-5) Example 6 (A-6) Example 7 (A-7) Example 8 (A-8) Example 9 (A-9) Example 10 (A-10) Example 11 (A-1: 1st Micronization)+ (A-11: 4th Micronization) Example 12 (A-1: 1st micronization)+(A-2: 4th micronization) Example 13 (A-12) Example 14 (A-13) Example 15 (A-12: 1st micronization)+(A-13: 1st micronization) Example 16 (A-12) Comparative Example 1 No additives used Comparative Example 2 Monobutyl Maleate Comparative Example 3 Monolauryl Glutarate Comparative Example 4 Dodecanoic Acid Comparative Example 5 Stearic Acid Comparative Example 6 Pluronic L35 Comparative Example 7 No additives used (pre-neutralization process) Comparative Example 8 laureth-3-adipate Comparative Example 9 Polyethyleneglycol Monomethacrylate (bisomer PEM6LD)

[0423] Test example

[0424] For the superabsorbent resin compositions prepared in the above examples and comparative examples, particle aggregation characteristics, centrifugal retention capacity (CRC), pressurized absorption capacity (AUP), absorption rate, and effective absorption capacity were measured, respectively, using the methods described below, and the results are shown in Tables 3 and 4 below. Unless otherwise noted, all evaluations of the physical properties below were conducted in a constant temperature and humidity chamber (23±2℃, relative humidity 45±10%), and the average of three measurements was used as the measurement data to prevent measurement errors. Furthermore, in the evaluations of physical properties below, physiological saline or brine refers to a 0.9 wt% aqueous sodium chloride (NaCl) solution.

[0426] (1) Evaluation of particle aggregation characteristics

[0427] ① 1,000 g of the unneutralized polymer of Step 1 (moisture content 70 wt%) prepared in each example and comparative example was prepared.

[0428] ② Next, 0.36 g of the additive of Formula 1 or the corresponding comparative compound was water-dispersed in 17.54 g of water at 80°C (preparation of a 2.04 wt% water dispersion), and this was mixed with 300 g of the polymer obtained in Step 1.

[0429] The additive of Step 2 above or the corresponding comparative compound was mixed in the form of an aqueous solution according to the type and amount used in each example and comparative example.

[0430] ② 300g of the above mixture was fed into a mincer containing a 3mm Ψ hole and a 5T thick perforated plate and ground.

[0431] ③ For the above-mentioned crushed material, a visual aggregation evaluation was conducted based on the discharge time, discharge amount, and the evaluation criteria in Table 2 below, and the results were recorded in Table 3.

[0432] At this time, the discharge time refers to the time (in seconds) it takes to discharge 200g of ground material from the mincer, and the discharge time is shortened as the aggregation is reduced.

[0433] The discharge amount refers to the ratio (wt%) of the content discharged through the discharge port to the 300g mixture introduced after the above step ② is completed, and as the aggregation is relieved, the amount of lumps remaining inside the grinder decreases, and the discharge amount increases.

[0434] In addition, photos serving as examples of evaluation items ○ and X for visual aggregation evaluation are shown in Figures 2 (a) and (b), respectively.

[0435] evaluation standard X More than 80% of the extruded material is extruded in the form of strands longer than 1 cm (see Fig. 2(a)). Due to the high adhesion to the blade, the polymer is crushed during chopping, resulting in a rough surface of the granules, and due to high cohesion, more than 80% of the extruded material has a strand shape longer than 1 cm. ○ More than 80% of the extruded material is extruded in the form of particles smaller than 1 cm (see Fig. 2(b)). The adhesion and cohesion forces to the blade are significantly reduced, resulting in a smooth surface of the granules after chopping, and more than 80% of the extruded material has a shape close to spherical, smaller than 1 cm.

[0436] Types of additives Evaluation of particle aggregation characteristics Discharge time (seconds) Discharge volume (wt%) Visual cohesion assessment Experimental Example 1-1 A-1 24 97.3 ○ Experimental Example 1-2 A-2 55 95.6 ○ Experimental Example 1-3 A-3 60 93.3 ○ Experimental Example 1-4 A-4 61 92.6 ○ Experimental Example 1-5 A-5 185 68.3 ○ Experimental Example 1-6 A-6 165 71.6 ○ Experimental Example 1-7 A-7 23 99.3 ○ Experimental Example 1-8 A-8 184 72.6 ○ Experimental Example 1-9 A-9 108 79.0 ○ Experimental Example 1-10 A-10 35 97.3 ○ Experimental Example 1-11 A-12 180 69.4 ○ Experimental Example 1-12 A-13 178 70.1 ○ Comparative Experiment Example 1-1 No additives Over 300 seconds 30.6 X Comparative Experiment Example 1-2 Monobutyl Maleate Over 300 seconds 34 X Comparative Experiment Examples 1-3 Monolauryl Glutarate Over 300 seconds 34.6 X Comparative Experiment Examples 1-4 Dodecanoic Acid Over 300 seconds 31 X Comparative Experiment Examples 1-5 Stearic Acid Over 300 seconds 30.3 X Comparative Experiment Examples 1-6 Pluronic L35 Over 300 seconds 37 X Comparative Experiment Examples 1-8 laureth-3-adipate Over 300 seconds 35 X Comparative Experiment Examples 1-9 Polyethyleneglycol Monomethacrylate (bisomer PEM6LD) Over 300 seconds 25 X

[0437] Referring to Table 3 and Figure 2 above, it was confirmed that when grinding is performed by adding an unneutralized polymer and an additive of Formula 1 of the present invention, compared to cases where such additive is not used or a compound that does not conform to the structure is used, the aggregation between particles after grinding is suppressed, resulting in a shorter discharge time and an excellent discharge volume. In addition, it was confirmed that the adhesion and aggregation forces of the mixtures introduced into the mixer are mitigated by the additive of Formula 1 of the present invention, and that more than 80% of the discharged material is discharged in the shape of 1 cm particles during visual evaluation.

[0439] (2) Centrifuge Retention Capacity (CRC)

[0440] The water retention capacity of each resin composition based on the absorption ratio under no load was measured according to the European Disposables and Nonwovens Association (EDANA) standard EDANA WSP 241.3.

[0441] Specifically, from the superabsorbent resin compositions obtained through the examples and comparative examples, a resin classified by a #30-50 sieve was obtained. This resin W0 (g) (about 0.2g) was uniformly placed into a nonwoven bag and sealed, then immersed in physiological saline solution (0.9 wt%) at room temperature. After 30 minutes, the water was drained from the bag for 3 minutes under conditions of 250g using a centrifuge, and the mass W2 (g) of the bag was measured. In addition, the same operation was performed without using the resin, and the mass W1 (g) was measured.

[0442] Using each obtained mass, the CRC(g / g) was calculated according to the following mathematical formula 1, and the results were recorded in Table 4.

[0443] [Mathematical Formula 1]

[0444] CRC (g / g) = {[W2(g) - W1(g)] / W0(g)} - 1

[0446] (3) Absorbency under Pressure (AUP)

[0447] The pressurized absorption capacity of the superabsorbent resin compositions of the above examples and comparative examples at 0.7 psi was measured according to the EDANA method WSP 242.3.

[0448] First, when measuring pressurized absorption capacity, the resin classifier from the above CRC measurement was used.

[0449] Specifically, a stainless steel 400 mesh wire mesh was mounted on the bottom of a plastic cylinder with an inner diameter of 25 mm. Under conditions of room temperature and 50% humidity, an absorbent resin composition W0 (g) (0.16 g) was uniformly spread over the wire mesh, and a piston capable of uniformly applying a load of 0.7 psi was positioned so that its outer diameter was slightly smaller than 25 mm, there was no gap with the inner wall of the cylinder, and its vertical movement was not obstructed. At this time, the weight W3 (g) of the device was measured.

[0450] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed on the inside of a petroleum dish with a diameter of 150 mm, and physiological saline solution composed of 0.9 wt% sodium chloride was placed at the same level as the top surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of it. The measuring device was placed on the filter paper, and the liquid was absorbed under load for 1 hour. After 1 hour, the measuring device was lifted, and its weight W4 (g) was measured.

[0451] Using each mass obtained, the pressurized absorption capacity (g / g) was calculated according to the following mathematical formula 2, and the results were listed in Table 4.

[0452] [Mathematical Formula 2]

[0453] AUP(g / g) = [W4(g) - W3(g)] / W0(g)

[0455] (4) Surface tension (S / T)

[0456] To measure the surface tension of the superabsorbent resin compositions of the above examples and comparative examples, 0.5 g of each superabsorbent resin composition was added to 40 mL of 0.9% saline solution and stirred at 350 rpm for 3 minutes, after which stirring was stopped to obtain saline solution containing the swollen superabsorbent resin. Using the saline solution as a measurement sample, the surface tension of each superabsorbent resin composition was measured using a surface tension meter (Product name: Force Tensiometer-K100, manufactured by KRUSS), and the results are listed in Table 4.

[0458] (5) Bulk density (BD)

[0459] 100 g of the superabsorbent resin composition of the above examples and comparative examples was poured through the orifice of a standard flow rate measuring device and received into a container with a volume of 100 ml. The superabsorbent resin composition was leveled to adjust the volume of the superabsorbent resin composition to 100 ml, and then the weight of the superabsorbent resin composition alone, excluding the container, was measured. Then, the weight of the superabsorbent resin composition alone was divided by the volume of the superabsorbent resin composition, 100 ml, to obtain the apparent density corresponding to the weight of the superabsorbent resin composition per unit volume.

[0461] (6) Differential generation amount

[0462] The amount of fine particles generated from the superabsorbent resin compositions of the above examples and comparative examples was calculated as the ratio of the weight of resin having a particle size of less than 150 μm to the total weight after passing the prepared superabsorbent resin composition through a coarse grinder (conditions of 2800 rpm, 0.4 mm clearance, and 1 mm bottom mesh) once, and the results are listed in Table 4.

[0464] (7) Absorption rate (Vortex time)

[0465] The absorption rate (vortex time) of the superabsorbent resin compositions of the above examples and comparative examples was measured in the following manner, and the results are listed in Table 4.

[0466] ① First, 50 mL of 0.9% saline solution was added to a 100 mL beaker with a flat bottom using a 100 mL mass cylinder.

[0467] ② Next, the beaker was placed in the center of the magnetic stirrer, and a magnetic bar (diameter 8 mm, length 30 mm) was placed inside the beaker.

[0468] ③ Afterwards, the stirrer was operated so that the magnetic bar stirred at 600 rpm, and the lowest part of the vortex generated by stirring was brought into contact with the top of the magnetic bar.

[0469] ④ After confirming that the temperature of the brine in the beaker reached 24.0℃, a sample of 2±0.01 g of the superabsorbent resin composition was added while simultaneously starting a stopwatch. The time until the vortex disappeared and the liquid surface became completely horizontal was measured in seconds, and this was defined as the absorption rate.

[0471] division SAP properties CRC(g / g) AUP(g / g) S / T(mN / m) BD(g / ml) Differential generation amount (%) Absorption rate (seconds) Experimental Example 2-1 Example 1 43.5 27.4 71.5 0.72 1.4 23 Experimental Example 2-2 Example 2 42.5 27.3 71.1 0.71 2.3 25 Experimental Example 2-3 Example 3 42.3 26.5 71.2 0.71 2.7 26 Experimental Example 2-4 Example 4 42.1 27.3 71.3 0.72 4.8 30 Experimental Example 2-5 Example 5 41.6 27.0 71.2 0.71 3.5 29 Experimental Example 2-6 Example 6 41.4 26.9 71.3 0.71 3.2 29 Experimental Example 2-7 Example 7 42.4 27.4 71.4 0.72 4.3 28 Experimental Example 2-8 Example 8 42.0 27.0 71.0 0.70 5.2 28 Experimental Example 2-9 Example 9 41.8 26.8 71.1 0.70 3.0 27 Experimental Example 2-10 Example 10 42.2 27.4 70.9 0.70 1.9 24 Experimental Example 2-11 Example 11 43.4 27.5 71.2 0.71 1.1 22 Experimental Example 2-12 Example 12 42.6 26.8 71.0 0.71 1.2 21 Experimental Example 2-13 Example 13 40.5 24.3 71.0 0.70 4.4 30 Experimental Example 2-14 Example 14 41.8 25.3 71.1 0.71 2.5 28 Experimental Example 2-15 Example 15 40.9 24.5 71.1 0.71 4.0 30 Experimental Example 2-16 Example 16 42.1 25.8 71.1 0.71 3.1 28 Comparative Experiment Example 2-1 Comparative Example 1 37.7 25.5 71.1 0.69 14.5 38 Comparative Experiment Example 2-2 Comparative Example 2 38.3 25.0 _ _ 15.1 35 Comparative Experiment Example 2-3 Comparative Example 3 36.8 25.7 68.9 0.68 16.2 36 Comparative Experiment Example 2-4 Comparative Example 4 37.0 25.5 68.1 0.68 16.3 36 Comparative Experiment Example 2-5 Comparative Example 5 37.8 25.3 _ _ 14.9 35 Comparative Experiment Example 2-6 Comparative Example 6 38.5 25.0 _ _ 11.7 35 Comparative Experiment Example 2-7 Comparative Example 7 36.7 24.3 71.3 0.68 15.4 40 Comparative Experiment Example 2-8 Comparative Example 8 38.5 25.1 70.5 0.69 13.5 34 Comparative Experiment Example 2-9 Comparative Example 9 35.9 24.5 - - 16.7 42

[0472] Referring to Table 4 above, when a superabsorbent resin composition is prepared by adding an additive of Formula 1 of the present invention to an unneutralized polymer, compared to cases where such additive is not used, where a compound that does not conform to the structure is used, or where it is mixed with a neutralized hydrogel polymer, aggregation between particles after grinding is suppressed. This allows for the preparation of a composition containing superabsorbent resin particles of a desired particle size without an additional grinding process after drying, and consequently, the amount of fine powder generated is reduced. Accordingly, it can be confirmed that the superabsorbent resin composition of the present embodiment has a significantly faster absorption rate compared to the comparative example, possesses water retention capacity and pressurized absorption capacity at an equivalent or higher level, and simultaneously exhibits a high bulk density without a decrease in surface tension.

Claims

Claim 1 A superabsorbent resin composition comprising: superabsorbent resin particles comprising a crosslinked polymer of a water-soluble ethylene-based unsaturated monomer having an acidic group and an internal crosslinking agent; and an additive represented by the following chemical formula 1, wherein the additive is included in an amount of 0.1 to 3 parts by weight per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer, and the apparent density of the superabsorbent resin composition is 0.70 g / ml or higher: [Chemical Formula 1] In the above chemical formula 1, A1, A2, and A3 each independently have a single bond, carbonyl, , or and, provided that one or more of these are carbonyl or and, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and is connected to adjacent R1, R2 and R3, respectively, and R1, R2 and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and n is an integer from 1 to 9. Claim 2 A superabsorbent resin composition according to claim 1, wherein the additive is one or more selected from compounds represented by the following chemical formulas 1-1 to 1-14: [Chemical Formula 1-1] [Chemical Formula 1-2] [Chemical Formula 1-3] [Chemical Formula 1-4] [Chemical Formula 1-5] [Chemical Formula 1-6] [Chemical Formula 1-7] [Chemical Formula 1-8] [Chemical Formula 1-9] [Chemical Formula 1-10] [Chemical Formula 1-11] [Chemical Formula 1-12] [Chemical Formula 1-13] [Chemical Formula 1-14] . Claim 3 delete Claim 4 A superabsorbent resin composition according to claim 1, further comprising a surface crosslinked layer formed by additionally crosslinking the crosslinked polymer on at least a portion of the surface of the superabsorbent resin particles through a surface crosslinking agent. Claim 5 In claim 1, the superabsorbent resin composition is a superabsorbent resin composition having an absorption rate (vortex time) of 30 seconds or less at 24.0°C according to the vortex method. Claim 6 In claim 1, the superabsorbent resin composition is a superabsorbent resin composition having a centrifugal retention capacity (CRC) of 39.0 g / g or more according to EDANA WSP 241.

3. Claim 7 In claim 1, the superabsorbent resin composition is a superabsorbent resin composition having an applied absorption capacity (AUP) of 24.0 g / g or more at 0.7 psi according to the EDANA method WSP 242.

3. Claim 8 A method for preparing a superabsorbent resin composition comprising: a step of forming a polymer by crosslinking a water-soluble ethylene-based unsaturated monomer having an acidic group in the presence of an internal crosslinking agent and a polymerization initiator (Step 1); a step of neutralizing at least some of the acidic groups of the polymer (Step 2); a step of preparing base resin particles by micronizing the polymer in the presence of an additive represented by the following Chemical Formula 1 (Step 3); and a step of drying the base resin particles (Step 4), wherein the additive is included in an amount of 0.1 to 3 parts by weight per 100 parts by weight of the water-soluble ethylene-based unsaturated monomer, and the apparent density of the superabsorbent resin composition is 0.70 g / ml or higher: [Chemical Formula 1] In the above chemical formula 1, A1, A2, and A3 each independently have a single bond, carbonyl, , or and, provided that one or more of these are carbonyl or and, where, m1, m2 and m3 are each independently integers from 1 to 8, and Each is connected to an adjacent oxygen atom, and is connected to adjacent R1, R2 and R3, respectively, and R1, R2 and R3 are each independently hydrogen, a straight-chain or branched-chain alkyl having 6 to 18 carbon atoms, or a straight-chain or branched-chain alkenyl having 6 to 18 carbon atoms, and n is an integer from 1 to 9. Claim 9 A method for manufacturing a superabsorbent resin composition, wherein the step of forming the polymer (step 1) is performed in a batch-type reactor. Claim 10 A method for manufacturing a superabsorbent resin composition according to claim 8, wherein steps 2 and 3 are performed sequentially, simultaneously, or alternately. Claim 11 delete Claim 12 A method for manufacturing a superabsorbent resin composition according to claim 8, wherein the step of manufacturing the base resin particles (step 3) is performed using a micronizing device, and the micronizing device comprises: a body part including a transfer space in which a mixture of a polymer and an additive is transferred; a screw member rotatably installed inside the transfer space to move the mixture; a drive motor providing rotational driving force to the screw member; and a cutter member installed in the body part and including a porous plate having a plurality of holes formed therein, and crushing the mixture while discharging it to the outside of the body part. Claim 13 A method for manufacturing a superabsorbent resin composition according to claim 8, wherein steps 2 and 3 are performed sequentially, simultaneously, or alternately, and steps 2 and 3 are performed using a micronizing device, wherein the micronizing device further comprises: a body part including a transfer space in which a mixture of a polymer and an additive is transferred; a screw member rotatably installed inside the transfer space to move the mixture; a drive motor providing rotational driving force to the screw member; a cutter member installed in the body part and including a porous plate having a plurality of holes formed therein, which grinds the mixture while discharging it to the outside of the body part; and a neutralizing agent spray nozzle installed inside the body part. Claim 14 A method for manufacturing a superabsorbent resin composition according to claim 13, wherein a neutralizing agent is injected into the body portion through the neutralizing agent injection nozzle in the above-mentioned atomizing device to neutralize at least some of the acidic groups of a polymer having acidic groups in the mixture. Claim 15 A method for manufacturing a superabsorbent resin composition according to claim 12, wherein the hole size formed in the porous plate is 0.1 mm to 30 mm. Claim 16 A method for manufacturing a superabsorbent resin composition according to claim 8, wherein the step of drying the base resin particles (step 4) is performed in a moving type. Claim 17 A method for manufacturing a superabsorbent resin composition according to claim 8, wherein the step of drying the base resin particles (step 4) is performed using a moving type dryer such as a horizontal-type mixer, rotary kiln, paddle dryer, or steam tube dryer. Claim 18 A method for preparing a superabsorbent resin composition according to claim 8, wherein the moisture content of the superabsorbent resin particles obtained in the step of drying the base resin particles (step 4) is 10% to 20% by weight. Claim 19 A method for preparing a superabsorbent resin composition according to claim 8, further comprising the step of forming a surface crosslinking layer on at least a portion of the surface of the superabsorbent resin particles prepared in step 4 in the presence of a surface crosslinking agent.

Citation Information

Patent Citations

  • Absorbing resin particle and manufacturing method thereof

    JP2011190426A

  • Water-absorbing polymer particles with improved colour stability

    KR1020130096218A

  • Method for producing absorbent resin powder and apparatus for producing the same

    KR1020190077541A

  • Complex minute cutting apparatus for super absorbent polymer hydrous gel

    KR1020210062459A

  • Water-absorbent resin particles and method for producing same

    WO2020137241A1